A new extinct species of Snipe (Aves: Scolopacidae: Gallinago) from the West Indies - Steadman, David W.; Takano, Oona M. (Zootaxa, 2016)
We describe an extinct species of snipe (Gallinago kakuki, new species) from late Quaternary fossils in the Bahamian Archipelago (Abaco, New Providence, Little Exuma, Long, and Middle Caicos islands). The new species is known as well from fossils on Cuba, and Cayman Brac in the Cayman Islands. This rather large species of snipe was volant, although because of its relatively short carpometacarpus, the primary flight feathers probably were short. The only other species of Gallinago from the West Indies is the extant, migratory G. delicata, which breeds only in North America. Gallinago kakuki shares more osteological characters with two Eurasian species (G. media, G. hardwickii) than with either of the New World species we examined (G. delicata, G. paraguaiae). A possible inter-hemispherical relationship has been proposed as well for the two extinct, late Quaternary species of woodcocks from the West Indies (Scolopax anthonyi of Puerto Rico, S. brachycarpa of Hispaniola).